HUBUNGAN ANTARA BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Leli Nurjanah (UNISAN JURNAL, 2024)
The aim of this research is to determine the Leadership of the Head of the Madrasah Study on Teacher Discipline at SMAN 1 Gunung Sugih, Gunung Sugih District, Central Lampung Regency. This type of research is qualitative descriptive research. The data sources are madrasah principals and their deputies, teachers and students who were selected purposively and using snowball sampling. The data collection techniques used were observation, unstructured interviews and documentation. The data analysis technique used is inductive, with the steps: reducing data, presenting data, and verifying data. The results of this research show that teacher discipline at SMAN 1 Gunung Sugih, Gunung Sugih District, Central Lampung Regency is quite good as evidenced by 1) the majority of teachers comply with madrasa rules, 2) the majority of teachers are diligent in teaching, 3) the majority of teachers are punctual in teaching. , 4) most teachers never leave the classroom before the lesson ends. The teacher’s discipline is because the head of SMAN 1 Gunung Sugih, Gunung Sugih District, Central Lampung Regency is able to carry out his role as a good administrator, supervisor and motivator, with the findings (1) as an administrator in (a) making himself a good role model, (b) being open , and (c) creating a conducive work climate. (2) as a supervisor (a) provides guidance to teachers in improving the quality of learning, (b) supervises teacher performance, (c) increases cooperation with students’ parents, (d) evaluates teacher work results, and (e) follow up on the results of teacher performance evaluations continuously. (3) as a motivator (a) giving autonomy to teachers to develop goals, materials, methods, media and evaluation of their learning, (b) providing guidance and assistance in developing teacher competency, (c) involving teachers in every madrasah activity, (d ) accept and provide support for teachers who have creative ideas, and (e) provide strict rewards and sanctions Keywords: Work Culture, Work Motivation, Teacher Performance